2018
DOI: 10.1038/s41598-018-21910-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bld-1-Embedded Elastin-Like Polypeptides in Tumor Targeting

Abstract: Expression of various molecules on the surface of cancer cells compared to normal cells creates a platform for the generation of various drug vehicles for targeted therapy. Multiple interactions between ligands and their receptors mediated by targeting peptide-modified polymer could enable simultaneous delivery of a drug selectively to target tumor cells, thus limiting side effects resulting from non-specific drug delivery. In this study, we synthesized a novel tumor targeting system by using two key elements:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The 23-mer LP was genetically fused to the N-terminus of an elastin-like polypeptide (ELP) termed A96 ( Table 1 ). Emerging as an attractive recombinant protein–polymer choice for diverse applications, ELPs are under exploration as a drug delivery platform since their biosynthesis produces pharmacologically relevant, monodisperse, biodegradable, and biocompatible entities [ 20 , 21 , 22 ]. The sequence confirmed cDNA encoding the LP-A96 fusion protein was subjected to heterologous expression via bacterial fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…The 23-mer LP was genetically fused to the N-terminus of an elastin-like polypeptide (ELP) termed A96 ( Table 1 ). Emerging as an attractive recombinant protein–polymer choice for diverse applications, ELPs are under exploration as a drug delivery platform since their biosynthesis produces pharmacologically relevant, monodisperse, biodegradable, and biocompatible entities [ 20 , 21 , 22 ]. The sequence confirmed cDNA encoding the LP-A96 fusion protein was subjected to heterologous expression via bacterial fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Their research showed that B 5 V 60 had good binding ability with bladder tumor cells and can accumulate in tumor cells. After intravenous injection of B 5 V 60 , it showed good localization in mice with bladder tumor transplantation tumors …”
Section: Peptides Acting On Tme Componentsmentioning
confidence: 99%
“…Despite the significant advantages and success achieved by introducing PEG and HSA in target proteins, a highly efficient, cost-effective and reliable precision genetically designed protein-polymer fusion complex with high yield, specificity, bioactivity and well sustained pharmacodynamics and pharmacokinetics is required. The emergence of ELPs as a classical binding module to facilitate the fusion and delivery of therapeutic molecules or provide a surface site for the attachment and display of PDs to increase pharmacokinetic properties has become the subject of intense research focus [ 50 , 51 ]. Thus, by using ELPs as a delivery module, target molecular drugs or peptide drugs can be encapsulated, attached or displayed on the surface of ELP nanoparticles.…”
Section: Elps Increase the Pharmacokinetic Properties Of Therapeutic ...mentioning
confidence: 99%